Sustainable hole-making in a titanium alloy using throttle and evaporative cryogenic cooling and micro-lubrication. (July 2021) - Iqbal, Asif; Zhao, Guolong; Zaini, Juliana; He, Ning; Nauman, Malik M.; Jamil, Muhammad; Suhaimi, Hazwani
Highlights: Effectiveness of using evaporative and throttle cryogenic coolants in titanium drilling is investigated. Throttle cooling favored tool life, productivity, cleanliness, energy consumption, and process cost. Evaporative cooling caused thick adhesion on drills and did not support any sustainability measure. Micro-lubrication also favored most of the sustainability measures but at a low productivity level. Pecking should not be used in drilling of low to medium depth holes in titanium alloys. Abstract: Titanium, being a structural material, undergoes drilling process frequently for its engineering applications. The superior mechanical properties of titanium alloys make hole-making a highly unsustainable process. The process is marred by high cutting forces, intense tool damage, high energy consumption, poor hole quality, and high process cost. The work presents an approach for viable and cleaner drilling of the difficult-to-cut material by investigating the effects of micro-lubrication and the following two options of cryogenic cooling: (1) evaporative cooling using liquid nitrogen and (2) throttle cooling using compressed carbon dioxide gas. Additionally, the effects of cutting speed and pecking – a technique actualized by rapidly retracting the twist drill by 2 mm at two levels of depth during thru-cutting of the holes – are also quantified. Pecking is not found to be favorable to any of the evaluated sustainability measures. Of the three cutting fluids testes, throttle cryogenic cooling yielded the most advantageous results. The coolant, because of its effective heat dissipation capability, yielded superior outcomes with respect to all the sustainability measures except surface quality. Micro-lubrication proved to be beneficial, at the low level of cutting speed, to specific cutting energy, surface quality, and process cost. Evaporative cryogenic cooling did not yield promising results. The runs employing evaporative coolant or the high level of cutting speed experienced thicker tool adhesions whereas those utilizing pecking showed signs of intense progressive wear. Moreover, the thrust force data indicated occurrence of thermal softening of the work material as the drills progressed through the hole-cutting process. From the holistic perspective of sustainability, it is recommended to adopt throttle cryogenic cooling, a medium-to-high level of cutting speed, and no-pecking for hole-making in the titanium alloy.